Effectiveness of topical peppermint oil on symptomatic treatment of chronic pruritus - Elsaie LT; El Mohsen AM; Ibrahim IM; Mohey-Eddin MH; Elsaie ML (Dove Medical Press, 2016)
Lotfy T Elsaie,1,† Abdelraouf M El Mohsen,1 Ibrahim M Ibrahim,1 Mahmoud H Mohey-Eddin,1 Mohamed L Elsaie2 1Department of Dermatology, Al Azhar University, 2Department of Dermatology, National Research Centre, Cairo, Egypt †Dr Lotfy T Elsaie passed away on December 17, 2014 Background: Pruritus is one of the commonest skin complaints. Peppermint oil can be effective in reducing the severity of such a condition.Aim: The aim of this study was to assess the efficacy of topically applied peppermint oil in the treatment of chronic pruritus.Subjects and methods: Fifty selected subjects diagnosed with chronic pruritus due to hepatic, renal, or diabetic cause were studied and divided into two groups of 25 patients each. Group I patients were instructed to hydrate the skin and then apply topical peppermint oil, while Group II patients applied petrolatum topically by hand; this application was done on the areas of pruritus, twice daily for 2 weeks. The severity of the itch was assessed and compared before and after the study by the 5-D itch scale (5D-IS). The results were analyzed by SPSS software. Statistical methods such as descriptive analysis, independent samples t-test, paired samples t-test, and chi-square test were employed.Results: There was a significant improvement regarding all studied individual parameters (5-D IS) for the peppermint oil users with no significance among petrolatum users. A comparison of total score of 5-D IS between patients of Group I and patients of Group II favored the improvement following the use of peppermint oil than using placebo (P-value <0.05).Conclusion: The topical treatment of chronic pruritus with peppermint oil is effective, easy to use, safe, cheap, and more acceptable for those whose topical and systemic treatments tend to be irritating, contraindicated, or less well tolerated. Keywords: pruritus, peppermint oil, itch